THE ROLE OF ISLAMIC EDUCATION TEACHERS AS AGENTS OF RELIGIOUS MODERATION IN THE ERA OF DIGITAL DISRUPTION - Toha Mamudi; Devid Dwi Erwahyudin; Nurisma Salsabila Zahra; Erlina Wardani (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
The development of digital technology in this era of disruption has had a major impact on the way people think, socialize, and practice religion in modern society. This digital transformation not only provides new opportunities for education, but also poses serious challenges to the understanding of religious values. Islamic Education teachers have a great responsibility to maintain a balance between technological advances and moderate, tolerant, and inclusive Islamic values. This study aims to analyze the role of Islamic Education teachers as agents of religious moderation amid the tide of digital disruption by examining various strategies and challenges faced in learning. This study uses a qualitative approach with a literature study method on twenty scientific sources published between 2015 and 2025. The results of the study show that Islamic Education teachers have three main roles, namely as facilitators of moderation values, role models in digital literacy, and socio-religious mediators. Strengthening digital competence, integrating religious moderation values into the curriculum, and cross-disciplinary collaboration are important strategies for strengthening religious moderation in the educational environment.